One-stage transanal endorectal pull-through for treatment of hirschsprung’s disease: impact of additional abdominal approach - Thien, Ho Huu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: The transanal one-stage endorectal pull-through (TOSEPT) procedure sometimes requires assistance by an abdominal approach to complete the operation. This study aims to rectify this by evaluating the impact of an assisted abdominal approach in the outcomes of the TOSEPT in children with HD. Methods: A retrospective study was conducted at surgical pediatric department of Hue central hospital. All consecutive medial records of patients operated on for HD in our department between June 2010 and June 2018 were retrieved and analysed. Results: 66/446 (14.79%) patients with HD who required TOSEPT with an additional abdominal approach to complete the operation for inclusion in this retrospective study.Length of the resected colon: 13.30 ± 3.45 cm (open group) and 19.70 ± 4.50 cm (laparoscopic group). Average operative time: 156 ± 12 minutes (open group) and 170 ± 14 minutes (laparoscopic group). No deaths or intra-operative complications were recorded in this study. No postoperative complicationoccuredin the laparoscopic group. Grade II complication based on Dindo-Clavien classification occurred in 14 (21.21%) of the open group and one (1.51%) grade III complication. The length of hospital stay was shorter in the laparoscopic group at 5 ± 1.5 days compared to 7 ± 2.5 daysfor the open group.All of the complications were grade I or II, mainly enterocolitis at3-monthfollow-up. Conclusion: Additional abdominal approach impacts on post-operative results of TOSEPT procedure for HD but not on outcome of disease. Laparoscopic surgery as the additional abdominal approach should be used to reduce the complications Keywords: Hirschsprung’s disease, Transanal one-stage endorectal pull-through, additional abdominal approach.